Translation and validation of the Eustachian Tube Dysfunction Questionnaire (ETDQ-7) into the Malay language / Lim Yi Wee ... [et al.] - Wee, Lim Yi; Ramli, Ramiza Ramza; Nik Othman, Nik Adilah; Redzyque Ramza Ramli, Redzyque Ramza (Faculty of Medicine, 2023)
Introduction: Chronic Eustachian tube dysfunction (ETD) is the pathophysiologic basis of many middle ear diseases. Unfortunately, there is a lack of diagnostic tools for this condition. The ETDQ-7 is basically a 7-item questionnaire that has been consistently studied and proven to be reliable and valid for the evaluation and diagnosis of Eustachian tube dysfunction. We aim to translate the ETDQ-7 into a Malay language version and determine its validity. Methods: This cross-sectional study was carried out in the Departme nt of Otorhinolaryngology, Head and Neck Surgery, University Sains Malaysia, from March 2020 until January 2021. A translated Malay language version of the ETDQ-7 (BM-ETDQ-7) was produced following rigorous forward and backward translation. The BM-ETDQ-7 underwent face validity (FV) testing in 10 patients. Following a satisfactory (0.83) FV index, 126 participants were recruited to complete the BM-ETDQ-7, including 60 participants with ETD and 66 healthy control participants. Participants grouped in ETD were those who had positive ETD complaints and abnormal tympanograms. A subset of participants from both groups repeated the BM ETDQ-7 within a time frame of 2 weeks. Results: Internal consistency testing of the translated ETDQ-7 yielded a Cronbach α value of 0.878. Test-retest reliability showed a good ICC coefficient (>0.9), and a good correlation (r > 0.8). The BM-ETDQ-7 showed good discrimination between both groups with a significantly higher total mean score (SD) of 26.12 (6.17) in the ETD group as compared to 11.94 (3.83) in the non-ETD group. A score of 17.5 was found to be the optimal value to differentiate both groups. Conclusion: The present study showed good reliability and validity of the BM-ETDQ-7 when applied to both ETD and healthy participants. We recommend the use of the BM-ETDQ-7 in clinical practice among the Malay language-speaking population.